1970
DOI: 10.1021/ja00711a025
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance studies of some low-spin d5 tris diimine complexes

Abstract: A detailed magnetic resonance investigation of the Fe(III), Ru(III), and Os(III) complexes with 2,2'bipyridyl and 1,10-phenanthroline has been carried out with the purpose of obtaining an accurate estimate of the dipolar contribution to the observed shifts, to establish, if possible, trends in and delocalization in this series of metal ion complexes and to compare our results for these t2g5 systems with the previously reported nickel(II) complexes with the same ligand. We find a large dipolar contribution to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
1
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 0 publications
7
126
1
1
Order By: Relevance
“…The actual value of 'Cs used in the fits shown in Figures 2 and 3 and the k bet values following from the above mentioned condition are given in Tables 2 and 3. The "s values obtained range between 8 and 21 ps and are in general agreement with NMR data for comparable Ru 3 +-complexes. For example a constant value of20 ps was evaluated by Doddrell et al [5] for Ru(acach in a field range from 0.2 to 6 T. More specifically, our linewidth analysis of the 'H-NMR spectra of Ru(bpyH+ and Ru(phen)j+ published by DeSimone and Drago [17] revealed that electron spin relaxation in the latter is about twice as fast as in the former, in fair accord with our magnetokinetic finding.…”
Section: Resultssupporting
confidence: 89%
“…The actual value of 'Cs used in the fits shown in Figures 2 and 3 and the k bet values following from the above mentioned condition are given in Tables 2 and 3. The "s values obtained range between 8 and 21 ps and are in general agreement with NMR data for comparable Ru 3 +-complexes. For example a constant value of20 ps was evaluated by Doddrell et al [5] for Ru(acach in a field range from 0.2 to 6 T. More specifically, our linewidth analysis of the 'H-NMR spectra of Ru(bpyH+ and Ru(phen)j+ published by DeSimone and Drago [17] revealed that electron spin relaxation in the latter is about twice as fast as in the former, in fair accord with our magnetokinetic finding.…”
Section: Resultssupporting
confidence: 89%
“…31,56,57 Dichloromethane was dried on a Grubbs-type solvent purification system. 58 Anhydrous 1,2-dichloroethane was purchased from Aldrich in a Sure/Seal bottle to ensure purity.…”
Section: Methodsmentioning
confidence: 99%
“…[65] Thin-layer chromatography (TLC) and column chromatography were performed with silicagel 60 F 254 (Merck) and silica gel 60, respectively.…”
Section: Methodsmentioning
confidence: 99%